Independent Poor Prognostic Factors for True Progression after Radiation Therapy and Concomitant Temozolomide in Patients with Glioblastoma: Subependymal Enhancement and Low ADC Value - Yoo, R.-E.; Choi, S.H.; Kim, T.M.; Lee, S.-H.; Park, C.-K.; Park, S.-H.; Kim, I.H.; Yun, T.J.; Kim, J.-H.; Sohn, C.H. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Subependymal enhancement and DWI have been reported to be useful MR imaging markers for identifying true progression. Our aim was to determine whether the subependymal enhancement pattern and ADC can differentiate true progression from pseudoprogression in patients with glioblastoma multiforme treated with concurrent chemoradiotherapy by using temozolomide.MATERIALS AND METHODS: Forty-two patients with glioblastoma multiforme with newly developed or enlarged enhancing lesions on the first follow-up MR images obtained within 2 months of concurrent chemoradiotherapy completion were included. Subependymal enhancement was analyzed for the presence, location, and pattern (local or distant relative to enhancing lesions). The mean ADC value and the fifth percentile of the cumulative ADC histogram were determined. A multiple logistic regression analysis was performed to identify independent factors associated with true progression.RESULTS: Distant subependymal enhancement (ie, extending >1 cm or isolated from the enhancing lesion) was significantly more common in true progression (n = 24) than in pseudoprogression (n = 18) (P = .042). The fifth percentile of the cumulative ADC histogram was significantly lower in true progression than in pseudoprogression (P = .014). Both the distant subependymal enhancement and the fifth percentile of the cumulative ADC histogram were independent factors associated with true progression (P = .041 and P = .033, respectively). Sensitivity and specificity for the diagnosis of true progression were 83% and 67%, respectively, by using both factors.CONCLUSIONS: Both the distant subependymal enhancement and the fifth percentile of the cumulative ADC histogram were significant independent factors predictive of true progression.CCRTconcurrent chemoradiotherapyGBMglioblastoma multiformeTMZtemozolomideRANOResponse Assessment in Neuro-Oncology